Pengaruh Kualitas Layanan Pelatihan Jarak Jauh Terhadap Kepuasan Peserta (Studi Pada Peserta Pelatihan Di Balai Diklat Keuangan Cimahi) - Eko Lestiyanto; Fitroh Hastanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research seeks to examine how the quality of distance learning services influences the satisfaction of training participants at the Regional Training Office of FETA – BDK Cimahi. A descriptive quantitative design with a survey technique was applied. Primary data were obtained through questionnaires distributed via Microsoft Forms to 110 participants of distance training programs from various ministries, institutions, and local governments. Service quality was assessed using the SERVQUAL model, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. These dimensions were broken down into nine independent variables that potentially influence participant satisfaction. The analysis involved validity and reliability testing, classical assumption checks, simple linear regression, and Importance–Performance Analysis (IPA). The results show that the quality of distance training services positively and significantly affects participant satisfaction (sig. 0.000 < 0.05). The Adjusted R² of 0.239 means service quality accounts for 23.9% of satisfaction variance, while 76.1% is influenced by other variables outside the model. The IPA method was also employed to assess participants’ satisfaction and comprehension of services offered by BDK Cimahi, as well as to identify which service quality aspects require enhancement to improve overall participant satisfaction. IPA also identifies service areas that need improvement to increase participant satisfaction. The IPA results reveal that the alignment of training materials with participants’ needs is a priority area requiring improvement, while responsiveness, accessibility and usability of training facilities, and instructors’ ability to provide guidance should be maintained. These findings suggest that improving service quality, particularly in ensuring the relevance of training content, is essential to enhancing participant satisfaction in distance training programs within public sector institutions.